Comparison of airway deposition distributions of particles in healthy and diseased workers in an Egyptian industrial site. (21st March 2017) - Füri, Péter; Hofmann, Werner; Jókay, Ágnes; Balásházy, Imre; Moustafa, Mona; Czitrovszky, Blanka; Kudela, Gábor; Farkas, Árpád
Abstract: The objective of this study is the prediction and comparison of airway deposition patterns of an industrial aerosol in healthy workers and workers suffering from silicosis. Mass concentrations and related size distributions of particulate matter were measured in the industrial area of Samalut in Minia, Egypt. A novel stochastic lung deposition model, simulating the symptoms of silicosis by chronic bronchial (Br) obstruction and emphysema in the acinar (Ac) region, was applied to compute mass deposition fractions, deposition density, deposition rate and deposition density rate distributions in healthy and diseased workers. In the case of healthy workers, both mass deposition fractions and deposition rates are highest in the first half of the Ac region of the lung, while the corresponding deposition density and deposition density rate distributions exhibit a maximum in the large Br airways. In the case of diseased lungs, bullous emphysema causes a large deposition peak in the region of the bronchioli respiratorii. Regional mass deposition fractions adopt maximum values in the extrathoracic region, except during mouth breathing for bullous emphysema, where Ac deposition can be the most prominent. In general, lung deposition is significantly higher in diseased than in healthy lungs. Indeed, workers suffering from silicosis receive significantly higher Ac doses than healthy workers exposed to the same aerosol. Thus, this illness may progress faster if a diseased worker remains in a strongly polluted area.